High-density electromyography activity in various hamstring exercises - Hegyi, A.; Csala, D.; Péter, A.; Finni, T.; Cronin, N. J. (Scandinavian Journal of Medicine & Science in Sports, 2019)
Proximal-distal differences in muscle activity are rarely considered when defining the activity level of hamstring muscles. The aim of this study was to determine the inter-muscular and proximal-distal electromyography (EMG) activity patterns of hamstring muscles during common hamstring exercises. Nineteen amateur athletes without a history of hamstring injury performed 9 exercises, while EMG activity was recorded along the biceps femoris long head (BFlh) and semitendinosus (ST) muscles using 15-channel high-density electromyography (HD-EMG) electrodes. EMG activity levels normalized to those of a maximal voluntary isometric contraction (%MVIC) were determined for the eccentric and concentric phase of each exercise and compared between different muscles and regions (proximal, middle, distal) within each muscle. Straight-knee bridge, upright hip extension, and leg curls exhibited the highest hamstrings activity in both the eccentric (40%-54%MVIC) and concentric phases (69%-85%MVIC). Hip extension was the only BF-dominant exercise (Cohen's d = 0.28 (eccentric) and 0.33 (concentric)). Within ST, lower distal than middle/proximal activity was found in the bent-knee bridge and leg curl exercises (d range = 0.53-1.20), which was not evident in other exercises. BFlh also displayed large regional differences across exercises (d range = 0.00-1.28). This study demonstrates that inter-muscular and proximal-distal activity patterns are exercise-dependent, and in some exercises are affected by the contraction mode. Knowledge of activity levels and relative activity of hamstring muscles in different exercises may assist exercise selection in hamstring injury management.